How effective the method of organizing society in enabling the education of people with disabilities during the corona pandemic - Masoud, Bandar Mohammed Awad (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the effectiveness of the method of community organization in providing services (economic, technical, and social) to enable education of people with disabilities during the Corona pandemic period from the perspective of students with disabilities. The study sample consisted of (336) male and female students with disabilities in the city of Makkah Al-Mukarramah in the Kingdom of Saudi Arabia, and the results showed that the effectiveness of using the method of community organization in providing economic services came to a high degree and with a relative weight of 93.44%, and the technical services came to a high degree and a relative weight 81.37%, and social services came in a high degree with a relative weight of 84.28% to enable the education of people with disabilities, and the results showed that there were no statistically significant differences in the effectiveness of the method of community organization in enabling education for people with disabilities due to the variable (age, gender, type of disability), while there are Statistically significant differences on the effectiveness of the method of community organization in enabling the education of people with disabilities during the Corona pandemic period due to demographic data (educational level, an attribute of The study came out with a set of recommendations, the most important of which is to enhance the role of the method of community organization in providing services, the requirements for educating people with special needs, and to achieve cooperation between community organization and community institutions and organizations, whether in the public or private sector, with the aim of providing the services and needs necessary for educating people with special needs.